Pengaruh profitabilitas dan likuiditas terhadap modal kerja - Nurilman Muhammad , Fadhil; Hendayana, Yana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study intends to identify and analyze the effect of profitability and liquidity ratios on working capital in food and beverage companies for the 2016-2019 period. This research has a population of 26 food and beverage companies listed on the Indonesia Stock Exchange (IDX). The sample was determined using the purposive sampling method and the results were 8 companies that matched the sample criteria. In processing research data, the SPSS 20 Software program was used. The test results showed that profitability partially had no effect on the working capital of food and beverage companies for the period 2016 – 2019 which was based on the discovery of t-count (-2.215) < t-table (2.042) and significance in the t-test of 0.035 < 0.05. Liquidity partially affects the working capital of food and beverage companies for the period 2016 – 2019 which is based on the discovery of t-counts (2.122) < t-table (2.042) and significance in the t-test of 0.042 < 0.05. Simultaneously, profitability and liquidity did not have a significant effect on working capital in food and beverage companies for the period 2016 – 2019 based on the discovery of an f-calculated value (2,863) which was below the f-table (3.32). Through this research, it is hoped that it will be able to contribute thoughts and images to management science and be used as input for companies in determining policies taken for the future.